Penerapan TAM dalam Evaluasi Penerimaan Aplikasi P-Care BPJS Pada Puskesmas di Kabupaten Gorontao Utara - Gobel, Jimilin; Dai, Roviana; Ahaliki, Budiyanto (AI Society & STMIK Indonesia, 2025)
P-Care BPJS is a web-based management information system that can be accessed through a web browser with the address https://pcarejkn.bpjs-kesehatan.go.id/eclaim/ which generally functions to check the validity of BPJS membership data. However, in its use, there was an inconvenience when using the P-Care BPJS application where the patient's social data entry failed, causing the P-Care BPJS officer to double-enter the patient's social data. Another problem found in the form of slow application performance when used which results in the length of work time and service response time by P-Care BPJS officers. This research was conducted to find out how far the acceptance of the existing P-Care BPJS application at Puskesmas in North Gorontalo district and what factors can affect user acceptance. This research uses descriptive quantitative methods and uses the TAM Model to measure user acceptance, the results of the analysis show that the P-Care BPJS application has been well received by users with an acceptance of 80.6.